(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
In this interview taken in May 2012 at New York University, André Lepecki offers a unique perspective on the development of Performance Studies at NYU. Being in fact the only current member of the department who has been first a Master and a PhD student, and later a professor in the same department, Lepecki has a first-hand and multifaceted view of the hallmarks of the New York tradition of Performance Studies, and of the changes that have characterized them during the past twenty years. Arrived at New York University in the early nineties, with a background primarily in anthropology and dance, here Lepecki familiarized with philosophy, performing art and “critical theory”. Analyzing the history of Performance Studies at NYU, Lepecki identifies three key stages or moments: the “epic” moment, the moment of the “signature”, and the moment of the “corporations”. Furthermore he recognizes in the present leanings a greater focus on “critical theory”, but also on “American Studies”, which, with the exception of the work done by Diana Taylor with her Hemispheric Institute of Performance and Politics, leaves little room for the global opening that characterized NYU during the past decades. In his view, today the department favors two main strands of studies: “everyday life performances” and “performing art”. Finally, reflecting on the ontology of performance, Lepecki sees in its “disappearing” the rich potential for its various forms of “reappearing”.